Taxonomy review of the genus Brachytrupes (Orthoptera: Gryllidae) with the description of a new species and key to the species - Simeu-Noutchom, Alain; Heller, Klaus-Gerhard; Nyobe, Philene Corinne Aude Um; Kekeunou, Sevilor (Zootaxa, 2023)
The taxonomy of the genus Brachytrupes Serville, 1838, known as Giant Burrowing Crickets is revised. Brachytrupes includes thirteen species, with B. megacephalus Lefebvre, 1827 designated as type species to promote nomenclature stability. Brachytrupes membranaceus Drury 1773, is regarded as a nomen dubium. Furthermore, the present study provides a description of a new species Brachytrupes bapaensis Simeu-Noutchom, Kekeunou & Heller sp. nov. from West Cameroon, together with a species identification key and geographic distribution. Brachytrupes bapaensis sp. nov. can be distinguished from all other species of the genus by its black-brown body, pronotum smooth and black with a yellow spot on the lateral margin, posterior pronotum as wide as the anterior. Moreover, calling song with the syllable period around 8 ms and the syllable repetition rate near 115 Hz have been recorded. This review has wide implications for the knowledge of edible insects as well as their distribution.